An almost ideal demand system analysis of fresh fish in Semarang, Indonesia - R. Abdullah, Nik Mustapha; Poerwono, Dwisetia (Taylor & Francis, 1994)
This paper presents results from estimating an Almost Ideal Demand System (AIDS) for meat and fresh fish in Semarang, Indonesia. The results provide the first empirical estimates of income (i.e., expenditure), own and cross-price elasticities of demand of important food items by households. Fish was found to be a necessity item while beef and chicken are luxury goods. Also, it was found that fish and chicken as well as beef and chicken are complementary goods but fish and beef tend to be substitutes.